Detection of small internal fatigue cracks in Ti‐6Al‐4V via synchrotron radiation nanocomputed tomography. Issue 9 (15th June 2022) - Xue, Gaoge; Tomoda, Yuta; Nakamura, Takashi; Fujimura, Nao; Takahashi, Kosuke; Yoshinaka, Fumiyoshi; Takeuchi, Akihisa; Uesugi, Masayuki; Uesugi, Kentaro
Abstract: Two types of synchrotron radiation computed tomography (SR‐CT)—projection CT (micro‐CT) and phase‐contrast imaging CT (nano‐CT)—were used to observe internal fatigue cracks in (α + β) Ti‐6Al‐4V alloy. Micro‐CT detected cracks in the specimen at ~1 μm spatial resolution, and the nano‐CT provided magnified images at ~200 nm spatial resolution. The crack initiation sites were clarified as the α‐phase for both the surface and internal cracks; however, their opening behaviors differed. A sharp crack tip was observed in the surface crack, and the crack tip opening displacement (CTOD) increased with an increase in the applied load. By contrast, a blunted crack tip, similar to that of a crack in a vacuum, was observed for the internal crack, and its CTOD remained almost constant regardless of the applied load. These phenomena are likely to explain the different behaviors of surface and internal cracks, particularly the slower growth rate of internal cracks, which leads to a longer fatigue life in the very high cycle fatigue regime. Highlights: Small internal cracks with local microstructure were observed using nano‐CT in Ti‐6Al‐4V. Both surface and internal small cracks in Ti‐6Al‐4V initiated from the alpha phase. Surface cracks tips are sharper and more sensitive to external load than internal crack. Internal cracks have similar crack opening behaviors to those of cracks in a vacuum.